PENGARUH PERSEPSI HARGA DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN YANG DIMEDIASI KEPUASAN KONSUMEN - Ratlan Pardede; Tarcicius Yudi Haryadi (Universitas Bunda Mulia, 2017)
This study aims to determine the influence of the perception of price and product quality on consumer purchasing decisions which is mediated by satisfaction on Indomaret mini market Rorotan North Jakarta. Indomaret mini market is engaged in the retail sale of goods which needs to pay attention to the behavior of consumers to make decisions.This research is a quantitative survey approach that seeks to know how the influence of the perception of price and product quality on consumer purchasing decisions with customer satisfaction as an intervening variable. Data collection techniques are by using questionaire. The test instrument is used for testing the validity and reliability. As for the technique of data analysis, SEM is used. The study concludes : 1) price perception has a positive and significant effect on customer satisfaction, 2)price perception has not positive and significant effect on consumer purchasing decisions, 3) product quality has a positive and significant effect on customer satisfaction, 4) product quality has not positive and significant effect on consumer purchasing decisions, 5). consumer satisfaction has a positive and significant effect on consumer purchasing decisions, 6). Consumer satisfaction has effect on consumer purchasing decision to mediate price perception and product quality.Keywords: price, product, consumer satisfaction, consumer purchasing